Estudio de prefactibilidad para la fabricación de lentes de sol a base de plástico reciclado - Bocanegra Pizarro, Luis Alberto (2022)
In this project, a pre-feasibility study is developed for the implementation of a plant to produce sunglasses based on recycled plastic. The main objective of this writing is to determine if the implementation is feasible at the market level, technically and economically. The sunglasses that are made are products with a unique design that provide visual security, status and help you reduce your carbon footprint in the environment. In the second chapter, the in-depth market analysis is developed, investigating the apparent internal demand, which in this case is presented only with imports of sunglasses, and the supply that currently exists in the market. It was obtained that the demand was around 6 million units that grow annually. In chapter III, the possible location of the plant among three possible industrial locations in the national territory is presented, giving Lurín, as the preferred place for its construction. In chapter V and VI, you can see the development of the engineering study and the design of the production line in detail. In addition, the organization chart of the company. In chapter VII, the economic and financial profitability of the project is determined. With this, the benefits presented by the installation of a plant to produce sunglasses based on recycled plastic can be appreciated, such as the economic IRR of 36.72% and the financial IRR of 64.15%. In chapter VIII, the social benefit of the project is shown, through the presentation of social ratios such as the capital intensity, which for this project had an index of 0.23 and the capital density that showed an investment of 99,892.55 soles per position generated.